UPAYA MENINGKATKAN KETERAMPILAN MENULIS TEKS EKSPOSISI SEDERHANA MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING MUATAN PELAJARAN BAHASA INDONESIA KELAS V SDN LIDAH WETAN II/462 SURABAYA - Azizah, Lutfia Nur; Sulistyowati, Sulistyowati; Hendratno, Hendratno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Bahasa Indonesia as the language that unifies the nation is actually considered difficult to learn for the Indonesian people especially to master the language skills. Lack of ability to understand the writing and lack of writing skills can cause conflicts to arise. Expository texts require an understanding of an event but students cannot see it directly in observation, thereby they will find it more difficult to learn. Choosing the right learning model will help students learn any lesson, one of which is expository texts. Problem Based Learning is one of the most frequently used learning models because it is considered capable to improving student learning outcomes. This research aims to improve the ability to write simple expository texts as a result of student learning. It is hoped that this research can help students to explain things in good and correct written language, provide alternatives for teachers in teaching simple expository text lesson, and help schools develop curricula also improve overall student learning outcomes. This research used Classroom Action Research method with a Qualitative Approach. The results of research in cycle 1 showed that the average score was 73.75, which means they had not yet reached the minimum completeness criteria. Therefore, cycle 2 is needed for improvement actions. After being given action in cycle 2, it was found that the average score was 94.42, which means they had achieved the target determined at the beginning of the research. Therefore, there is no need to continue to cycle 3. Based on observations made during the learning process, students have become more proficient in writing good and correct spelling and punctuation so that learning outcomes can improve significantly.